Amyloid β Induces Early Changes in the Ribosomal Machinery, Cytoskeletal Organization and Oxidative Phosphorylation in Retinal Photoreceptor Cells - Deng, Liting; Pushpitha, Kanishka; Joseph, Chitra; Gupta, Veer; Rajput, Rashi; Chitranshi, Nitin; Dheer, Yogita; Amirkhani, Ardeshir; Kamath, Karthik; Pascovici, Dana; Wu, Jemma X.; Salekdeh, Ghasem Hosseini; et al. (Frontiers in Molecular Neuroscience, 2019)
Amyloid β (Aβ) accumulation and its aggregation is characteristic molecular feature of the development of Alzheimer’s disease (AD). More recently, Aβ has been suggested to be associated with retinal pathology associated with AD, glaucoma and drusen deposits in age related macular degeneration (AMD). In this study, we investigated the proteins and biochemical networks that are affected by amyloid β in the 661W photoreceptor cells in culture. Time and dose dependent effects of Aβ on the photoreceptor cells were determined utilising tandem mass tag (TMT) labelling-based quantitative mass-spectrometric approach. Bioinformatic analysis of the data revealed concentration and time dependent effects of the amyloid β peptide stimulation on various key biochemical pathways that might be involved in mediating the toxicity effects of the peptide. We identified increased Tau phosphorylation, GSK3β dysregulation and reduced cell viability in cells treated with Aβ in a dose and time dependent manner. This study has delineated for the first-time molecular networks in photoreceptor cells that are impacted early upon Aβ treatment and contrasted the findings with a longer-term treatment effect. Proteins associated with ribosomal machinery homeostasis, mitochondrial function and cytoskeletal organisation were affected in the initial stages of β-amyloid exposure, which may provide key insights into AD effects on the photoreceptors and specific molecular changes induced by Aβ peptide.